Implementation of a spiking neural network - Pacheco, E. (2013)
Reconfigurable systems allow the implementation of hardware using a Hardware Description Language (HDL). This allows a simple implementation and on-line reconfiguration, which are big advantages when compared to traditional electronic circuits, while maintain its main advantages: parallelism and speed. When an analogue system is considered, in this case a Field Programmable Analogue Array (FPAA), another advantage his added, the precision of the results. The neural networks allow fast outputs with low errors for complex systems.